2021
DOI: 10.32641/andespediatr.v92i6.4030
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of implementing the Paediatric Surviving Sepsis Campaign International Guidelines 2020 in resource-limited settings: A real-world view beyond the academia

Abstract: Las Guías Internacionales de la Campaña Sobreviviendo a la Sepsis para el Manejo del Shock Séptico y la Disfunción de Órganos Asociada a la Sepsis en Niños, fueron publicadas en 2020 y están desti- nadas a ser utilizadas en todos los lugares que atienden a niños. Sin embargo, los profesionales que atienden a los niños con sepsis en entornos con recursos limitados se enfrentan a una serie de desafíos y perfiles de enfermedad distintos a los que se encuentran en entornos ricos en recursos. Basándonos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Similarly, other investigators have suggested that the current guidelines for the treatment of paediatric sepsis may not be equally useful in the different regions where sepsis is frequent and that their recommendations should be adjusted to these realities. 22 Several subthemes that emerged in our study can also directly inform future CDS tool design and implementation. Participants emphasised the value of careful clinical assessments that include not only vital signs, but also metrics like perfusion/capillary refill and mental status.…”
Section: Open Accessmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, other investigators have suggested that the current guidelines for the treatment of paediatric sepsis may not be equally useful in the different regions where sepsis is frequent and that their recommendations should be adjusted to these realities. 22 Several subthemes that emerged in our study can also directly inform future CDS tool design and implementation. Participants emphasised the value of careful clinical assessments that include not only vital signs, but also metrics like perfusion/capillary refill and mental status.…”
Section: Open Accessmentioning
confidence: 88%
“…However, overcoming these challenges may improve dissemination and implementation of paediatric sepsis criteria and ultimately have a greater impact on paediatric sepsis outcomes. Similarly, other investigators have suggested that the current guidelines for the treatment of paediatric sepsis may not be equally useful in the different regions where sepsis is frequent and that their recommendations should be adjusted to these realities 22…”
Section: Discussionmentioning
confidence: 99%
“…); 2) доврачебные факторы (отсроченная диагностика, несо блюдение схем маршрутизации, ограниченные ресурсы медицинского учреждения); 3) факторы стационара (недо статочный штат и объем специализированных услуг, отсутствие оборудования, мониторинга, лекарств). Значительные различия в доступе к здравоохранению, наличии ресурсов, оказании медицинской помощи и ограниченной доказательной базе означают, что многие из имеющихся рекомендаций «Surviving Sepsis Campaign» неп рименимы или невыполнимы в клиниках с ограниченным финансированием [40,41]. По мнению F. Lorton et al (2022), неадекватные мероприятия интенсивной терапии могут быть связаны со следующим:…”
Section: анализ особеннос тей внедрения протоколированного лечения се...unclassified
“…Existen diversas guías y protocolos acerca de la administración de fluidos en las Unidades de Cuidados Intensivos (UCI) alrededor del mundo, los cuales brindan información y orientan al personal de salud sobre la manera de administrarlos en pacientes críticos 5,6 . Sin embargo, la forma en la que estos se suministran varía ampliamente entre cada UCI e incluso dentro de las mismas, dependiendo -muchas veces -del criterio específico de cada profesional y disponibilidad, especialmente en situaciones con recursos limitados 1,7,8 .…”
Section: Introductionunclassified